Government E-Service Delivery with Public-Private Partnership Approach in Rural Bangladesh: A Case Study on Mymensingh District - Sarker, Anupom (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This article provides a comprehensive examination and assessment of the e-services delivery of government through Union Digital Centers (UDCs). The emergence of electronic governance has resulted in the accelerated delivery of electronic services in different countries, including Bangladesh, with the aim of promoting socio-economic progress. Nonetheless, the notion of the “digital divide” or “digital gap” imposes constraints on its overall efficacy with e- services delivery as it exacerbates the socioeconomic disparity between affluent and impoverished individuals. In relation to the digital divide, existing literature indicates that tele-centers have predominantly been unsuccessful in reaching the intended demographic of the most impoverished individuals. The present study employed a survey methodology to gather data from a sample of 150 participants situated across 6 distinct Union Digital Centers (UDCs) of Mymensingh District. The results of the study suggest a favorable outcome with regards to the accessibility, affordability, convenience, and provision of services. However, it is imperative to enhance the implementation of Public-Private Partnerships (PPP) in order to achieve the desired outcomes in the field of e-governance.